2006
DOI: 10.1017/s1431927606063549
|View full text |Cite
|
Sign up to set email alerts
|

Using Electron Microscopy to Investigate Degradation of Candidate PEM Membranes due to Exposure to Fenton¡¦s Reagent

Abstract: Extended abstract of a paper presented at Microscopy and Microanalysis 2006 in Chicago, Illinois, USA, July 30 – August 3, 2006

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Weakley-Bollin found the skin thickness of his injection molded parts to be in the range of 2-10 μm. 8 Wang et al found the skin layer on injection molded polyolefin samples to be in the order of 10-50 μm for the processing conditions tested in their investigation. 11 However, Jansen reported the thickness of the skin layer to be in the range of 95-530 μm, depending on the resin flow rate during molding; a higher flow velocity corresponds to a lower skin thickness.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Weakley-Bollin found the skin thickness of his injection molded parts to be in the range of 2-10 μm. 8 Wang et al found the skin layer on injection molded polyolefin samples to be in the order of 10-50 μm for the processing conditions tested in their investigation. 11 However, Jansen reported the thickness of the skin layer to be in the range of 95-530 μm, depending on the resin flow rate during molding; a higher flow velocity corresponds to a lower skin thickness.…”
Section: Introductionmentioning
confidence: 93%
“…Some studies found that LCTE did not appear to be significantly affected by the measurement direction relative to resin flow, or location of the sample in respect to the injection gate. 3,8 On the other hand, another study did find that the LCTE for injection molded parts varied to some degree between the flow and transverse to flow directions, and that the thermal expansion for samples collected at the halfway point of the flow path appeared slightly larger than those collected near the gate or at the end of flow. 2 Zhang et al found the same to be true in his study on polyolefin blends.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation